The mechanism of formation of technology partnerships in industry - Yu. A. Deryabin (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the development of organizational and analytical tools for the mechanism of step-by-step formation of technological partnership in industry. The result of the research is a developed procedure for forming a technology partnership mechanism, which consists of five stages that allow determining the name and result of each of them. The proposed mechanism assumes at each stage the collection and analysis of information about the parameters of technological partnership of industrial enterprises, and also allows you to justify the list of consecutive directions of development of technological partnership, which determines the theoretical significance of the results obtained. For this purpose, they use methods of concept construction, logic, abstraction, description, and calculation method. The evaluation results determined within the relevant stages of the technological partnership mechanism serve as the basis for implementing regulatory measures by the subjects of the technological partnership to improve the regulatory and organizational and managerial conditions for the participation of industrial enterprises in the process of integrating technological decisions made within the framework of the technological partnership